Korean Versions of the Reading Test and Visual Perception Test for Children Treated for Unilateral Amblyopia - Che, Song-a; Yoo, Yung-Ju (Daihan angwa haghoi jabji, 2023)
Purpose: Reading speed and visual perception are used to evaluate visual function in children with amblyopia. This study used standardized tests to evaluate binocular reading performance and visual motor function in children treated for unilateral refractive amblyopia.Methods: In a prospective pilot study, reading and visual perception were evaluated in children aged 5-12 years who were diagnosed with unilateral refractive amblyopia between September 2020 and March 2021. To evaluate reading skills, the Readability Diagnostic Assessment and Korean Language-based Reading Assessment (KOLRA) were administered. The Korean version of the Developmental Test of Visual Perception-Third Edition (K-DTVP-3) test was used to evaluate visual perception function.Results: Reading ability and visual perception function were evaluated in 10 patients with unilateral refractive amblyopia. In the reading fluency test, the average reading speed of the patients was 185 ± 78.2 words per minute (WPM), and did not differ from that of the control group provided by KOLRA (p > 0.05). The general visual perception score was not significantly different from that of the controls. Among subtests of the K-DTVP-3, the hand coordination and figure-background tests scored 32.3 ± 17.7% and 29.9 ± 18.7%, respectively, lower than 50% of the normal average. The scores of the eye-hand coordination (r2 = 0.585, p = 0.01) and figure-background (r2 = 0.482, p = 0.03) tests were significantly correlated with the subject’s best-corrected visual acuity.Conclusions: In this study, there was no significant difference in reading fluency between the patients and controls. Among the K-DTVP-3 subtests, the average scores of the hand coordination and figure-background tests were lower than normal. Further studies are required to determine whether the reading fluency test and K-DTVP-3 reflect visual perception deficits in amblyopic patients.